2019
DOI: 10.3390/molecules24020340
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Oleanolic Acid (OA) Ameliorates Risk Factors of Cardiovascular Diseases in a Diet-Induced Pre-Diabetic Rat Model: Effects on Selected Cardiovascular Risk Factors

Abstract: The pathogenesis of prediabetes is associated with risk factors such as chronic consumption of an unhealthy diet. Recent studies have reported that diet-induced pre-diabetes is also associated with risk factors of cardiovascular complications, hence this study was aimed at evaluating the effects of oleanolic acid (OA) on pre-diabetes rats. Pre-diabetes was induced by chronic exposure of Sprague Dawley rats (SD) to high-fat high-carbohydrate diet (20 weeks), whereas the non-pre-diabetes control (NC) was given s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 60 publications
10
49
0
Order By: Relevance
“…46,47 Moreover, OA has also been reported to reduce the risk of developing cardiovascular disease by lowering LDL-C particles while increasing high-density lipoprotein cholesterol (HDL-C) particles. 16,17 These findings correlated with the previous study that reported that derivatives of OA such as 3-acetyl-oleanolic acid have also been shown to lower intrahepatic total cholesterol (TC), TGs and macrovesicular steatosis in high-fat diet-fed rats. 16,18,48 While the observed decrease in plasma TGs and VLDLs may partly be attributed to dietary intervention, it may also be ascribed to the insulinsensitizing effects of OA.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…46,47 Moreover, OA has also been reported to reduce the risk of developing cardiovascular disease by lowering LDL-C particles while increasing high-density lipoprotein cholesterol (HDL-C) particles. 16,17 These findings correlated with the previous study that reported that derivatives of OA such as 3-acetyl-oleanolic acid have also been shown to lower intrahepatic total cholesterol (TC), TGs and macrovesicular steatosis in high-fat diet-fed rats. 16,18,48 While the observed decrease in plasma TGs and VLDLs may partly be attributed to dietary intervention, it may also be ascribed to the insulinsensitizing effects of OA.…”
Section: Discussionsupporting
confidence: 88%
“…17 This condition is characterized by complications including hypertriglyceridemia, insulin resistance and hyperinsulinemia which are risk factors for the development of NAFLD. 16,24 The conventional management of NAFLD involves the combination of insulin sensitizers and lifestyle modification therapy which include exercise and dietary modification. 25 However, pharmacological therapy is normally prescribed during T2DM while low patient compliance has been reported with regard to lifestyle modifications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations